Men Superiority in Lynn Nottage's Play Ruined (2009) - Bebby Mutiara Emra; Desvalini Anwar (English Language and Literature, 2019)
The purpose of this analysis is to expose the issue of masculinity terror which have done through women in the Democratic Republic of Congo and to know the contribution of the character, plot/conflict, and setting in revealing the masculinity terror. This analysis is related to the feminist concept by Catharine MacKinnon that is supported by the text and context based interpretation. The result of this analysis shows the characters experience the masculinity terror that can be seen from their mental and physical condition.